2020
DOI: 10.1038/s41598-020-72356-1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous TALEN-mediated knockout of chrysanthemum DMC1 genes confers male and female sterility

Abstract: Genome editing has become one of the key technologies for plant breeding. However, in polyploid species such as chrysanthemum, knockout of all loci of multiple genes is needed to eliminate functional redundancies. We identified six cDNAs for the CmDMC1 genes involved in meiotic homologous recombination in chrysanthemum. Since all six cDNAs harbored a homologous core region, simultaneous knockout via TALEN-mediated genome editing should be possible. We isolated the CmDMC1 loci corresponding to the six cDNAs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 67 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…CYP73A encoded trans-cinnamate 4-monooxygenase, which converts cinnamic acid to p -coumaric acid through hydroxylation, whereas the CoA of p -coumaric acid is esterified by 4-Couramarate CoA (4CL) [ 42 ] and then converted to caffeoyl shikimic acid or caffeic acid in the presence of shikimate O-hydroxycinnamoyl transferase (HCT) or caffeoyl shikimate esterase (CSE) ( Figure 6 ), which is supportive of our results that p -coumaric acid, phenylacetate, and caffeic acid were significantly increased in the CC soil ( Figure 1 ). Conversely, the downregulation of COMT and CAD , which encoded caffeic acid 3-O-methyltransferase and cinnamyl-alcohol dehydrogenase, could inhibit lignin biosynthesis [ 43 ]. The p -coumaric acid, in turn, could be synthesized from more materials in this process.…”
Section: Discussionmentioning
confidence: 99%
“…CYP73A encoded trans-cinnamate 4-monooxygenase, which converts cinnamic acid to p -coumaric acid through hydroxylation, whereas the CoA of p -coumaric acid is esterified by 4-Couramarate CoA (4CL) [ 42 ] and then converted to caffeoyl shikimic acid or caffeic acid in the presence of shikimate O-hydroxycinnamoyl transferase (HCT) or caffeoyl shikimate esterase (CSE) ( Figure 6 ), which is supportive of our results that p -coumaric acid, phenylacetate, and caffeic acid were significantly increased in the CC soil ( Figure 1 ). Conversely, the downregulation of COMT and CAD , which encoded caffeic acid 3-O-methyltransferase and cinnamyl-alcohol dehydrogenase, could inhibit lignin biosynthesis [ 43 ]. The p -coumaric acid, in turn, could be synthesized from more materials in this process.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein 9 (Cas9) system is applicable in C. morifolium 5 . Recently, genome editing using the transcription activator-like effector nucleases (TALEN) system could simultaneously confer male and female sterility in C. morifolium 47 . However, it still requires enormous effort and a lot of time to determine target sequences for genome editing in C. morifolium .…”
Section: Discussionmentioning
confidence: 99%
“…However, polyploids such as chrysanthemum require a knockout of all loci of several genes to ensure the possibility of functional overlaps. Hence, Shinoyama et al (2020) identified complementary DNAs (cDNAs) for CmDMC1 genes, which were associated with meiotic homologous recombination in chrysanthemum [ 195 ]. Transcription activator-like effector nucleases (TALENS), an important genome-editing technology, was used to knock out all six identified CmDMC1 cDNAs that were found in a specific location on the chromosome.…”
Section: Advances In Genome Editing For Chrysanthemummentioning
confidence: 99%
“…Two chrysanthemum cultivars with the TALEN expression vector resulted in the development of lines with disruption of all CmDMC1 loci, successfully inducing male and female sterility. This study showed the efficacy of genome editing in the prevention of transgene flow [ 195 ]. Since whole genome sequence information of Chrysanthemum seticuspe is now available, the scope of genome editing studies in chrysanthemum to improve the ornamental attributes of chrysanthemum should be accelerated in the future [ 57 ].…”
Section: Advances In Genome Editing For Chrysanthemummentioning
confidence: 99%